2017
DOI: 10.17352/aprc.000017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat and Humidification on Aerosol Delivery during Auto-CPAP noninvasive Ventilation

Abstract: Objective: Although, the use of humidifi cation during non-invasive ventilation (NIV) is an important factor in decreasing nasal airway resistance and assuring patient's comfort and adherence; many in-vitro studies recommend switching off the humidifi er while delivering aerosol to NIV patients.The aim of the study was to in-vivo determine the effect of humidifi cation on salbutamol delivered via different inhalation devices to chronic obstructive pulmonary disease (COPD) patients using automatic continuous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 24 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Unlike the impact of humidification on aerosol delivery via MV, both in vivo and in vitro studies reported no significant effect of humidification on aerosol delivery via NIV, regardless of nebulizer types [ 97 , 98 , 101 ]. This difference may be explained by the lower temperatures and humidification of the inspired gas used during NIV than MV, as it traverses the nose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the impact of humidification on aerosol delivery via MV, both in vivo and in vitro studies reported no significant effect of humidification on aerosol delivery via NIV, regardless of nebulizer types [ 97 , 98 , 101 ]. This difference may be explained by the lower temperatures and humidification of the inspired gas used during NIV than MV, as it traverses the nose.…”
Section: Resultsmentioning
confidence: 99%
“…During NIV using a dual-limb circuit, little evidence about comparative nebulizer placement is available, nebulizer may be placed in the inspiratory limb the same way as in a dual-limb invasive ventilation circuit [94]. When placing the continuous nebulizer inline with NIV, both in vitro [91][92][93][95][96][97][98][99] and in vivo studies [100,101] reported higher inhaled doses with VMN than JN, regardless of the nebulizer placement and ventilator settings. In addition, JN is driven by an external compressed gas, which may affect the tidal volume and F I O 2 delivered by the ventilator, whereas these parameters are unlikely to be affected when VMN is utilized.…”
Section: Nebulizer Placementmentioning
confidence: 99%